Takayasu Arteritis: A Case Presenting With Neurological Symptoms and Proteinuria - Fatma AYDIN,; Banu ACAR,; Nermin UNCU,; Özge BAŞARAN,; Elçin ADALET YILDIZ,; Alev GÜVEN,; Nilgün ÇAKAR, (Archives of Rheumatology, 2020)
In this article, we present an 18-year-old female patient who was initially diagnosed as central nervous system vasculitis and focal segmental glomerulosclerosis but later diagnosed as Takayasu arteritis.